SPM add math formula list by majurie88

VIEWS: 315 PAGES: 16

• pg 1
```									                                                                                                 ONE-SCHOOL.NET
Add Maths Formulae List: Form 4 (Update 18/9/08)

01 Functions

Absolute Value Function                                             Inverse Function

If   y = f ( x ) , then f −1 ( y ) = x
f ( x ), if f ( x ) ≥ 0
f ( x)                                                    Remember:
− f ( x), if f ( x ) < 0                  Object = the value of x
Image = the value of y or f(x)
f(x) map onto itself means f(x) = x

General Form                                                        Quadratic Formula

ax 2 + bx + c = 0
−b ± b 2 − 4ac
where a, b, and c are constants and a ≠ 0.                                 x=
2a
*Note that the highest power of an unknown of a
quadratic equation is 2.                                                  When the equation can not be factorized.

Forming Quadratic Equation From its Roots:                          Nature of Roots

If α and β are the roots of a quadratic equation
b                             c
α +β =−                             αβ =                    b 2 − 4ac   >0    ⇔ two real and different roots
a                             a
b 2 − 4ac   =0    ⇔ two real and equal roots
The Quadratic Equation                                              b 2 − 4ac   <0    ⇔ no real roots
x 2 − (α + β ) x + αβ = 0                             b 2 − 4ac   ≥0    ⇔ the roots are real
or
x − ( SoR ) x + ( PoR ) = 0
2

SoR = Sum of Roots
PoR = Product of Roots

http://www.one-school.net/notes.html                            1
ONE-SCHOOL.NET

General Form                                                                 Completing the square:

f ( x) = ax 2 + bx + c                                      f ( x) = a ( x + p)2 + q

where a, b, and c are constants and a ≠ 0.                (i)     the value of x, x = − p
(ii)    min./max. value = q
*Note that the highest power of an unknown of a                 (iii)   min./max. point = (− p, q)
quadratic function is 2.                                        (iv)    equation of axis of symmetry, x = − p

Alternative method:
a > 0 ⇒ minimum ⇒ ∪ (smiling face)
f ( x) = ax 2 + bx + c
a < 0 ⇒ maximum ⇒ ∩ (sad face)
b
(i)     the value of x, x = −
2a
b
(ii)    min./max. value = f (−           )
2a
b
(iii)   equation of axis of symmetry, x = −
2a

Quadratic Inequalities                                       Nature of Roots

a > 0 and f ( x) > 0            a > 0 and f ( x) < 0
b 2 − 4ac > 0 ⇔ intersects two different points
at x-axis
a            b                   a            b            b − 4ac = 0 ⇔ touch one point at x-axis
2

b 2 − 4ac < 0 ⇔ does not meet x-axis

x < a or x > b                       a< x<b

04 Simultaneous Equations

To find the intersection point ⇒ solves simultaneous equation.

Remember: substitute linear equation into non- linear equation.

http://www.one-school.net/notes.html                     2
ONE-SCHOOL.NET
05 Indices and Logarithm

Fundamental if Indices                                   Laws of Indices

Zero Index,             a0 = 1                           a m × a n = a m+n
1
Negative Index,         a −1 =
a                       a m ÷ a n = a m−n
a
( ) −1 =
b                       ( a m ) n = a m× n
b       a

1                               ( ab) n = a n b n
Fractional Index        an   = a n

m                                a n an
an   = a n   m
( ) = n
b   b
Fundamental of Logarithm                                 Law of Logarithm

log a y = x ⇔ a x = y                                    log a mn = log a m + log a n

log a a = 1                                              log a
m
= log a m − log a n
n
log a a x = x
log a mn = n log a m
log a 1 = 0
Changing the Base

log c b
log a b =
log c a

1
log a b =
logb a

http://www.one-school.net/notes.html                 3
ONE-SCHOOL.NET
06 Coordinate Geometry

Distance Between Point A and C =
(x1 − x2 )2 + (x1 − x2 )2

y2 − y1
Gradient of line AC, m =
x2 − x1
Or
⎛ y − int ercept ⎞
Gradient of a line, m = − ⎜                ⎟
⎝ x − int ercept ⎠

Parallel Lines                                     Perpendicular Lines

When 2 lines are parallel,                            When 2 lines are perpendicular to each other,

m1 = m2 .                                            m1 × m2 = −1

m1 = gradient of line 1
m2 = gradient of line 2

Midpoint                                              A point dividing a segment of a line

⎛ x1 + x2 y1 + y2 ⎞                    A point dividing a segment of a line
Midpoint, M = ⎜        ,        ⎟                          ⎛ nx + mx2 ny1 + my2 ⎞
⎝ 2          2 ⎠                          P =⎜ 1       ,          ⎟
⎝ m+n        m+n ⎠

http://www.one-school.net/notes.html              4
ONE-SCHOOL.NET
Area of triangle:

Area of Triangle

1
=
2

1
A=
2
( x1 y2 + x2 y3 + x3 y1 ) − ( x2 y1 + x3 y2 + x1 y3 )

Form of Equation of Straight Line
General form                                      Gradient form                            Intercept form

ax + by + c = 0                                    y = mx + c                              x y
+ =1
a b
c = y-intercept                                                     b
a = x-intercept    m=−
b = y-intercept           a

Equation of Straight Line
Gradient (m) and 1 point (x1, y1) 2 points, (x1, y1) and (x2, y2) given                    x-intercept and y-intercept given
given
y − y1 = m( x − x1 )                 y − y1 y2 − y1                                             x y
=                                                    + =1
x − x1 x2 − x1                                             a b

Equation of perpendicular bisector ⇒ gets midpoint and gradient of perpendicular line.

Information in a rhombus:
A                                B
(i)         same length ⇒ AB = BC = CD = AD
(ii)        parallel lines ⇒ mAB = mCD or mAD = mBC
(iii)       diagonals (perpendicular) ⇒ mAC × mBD = −1
(iv)        share same midpoint ⇒ midpoint AC = midpoint
D                                                                 BD
C                       (v)         any point ⇒ solve the simultaneous equations

http://www.one-school.net/notes.html                                   5
ONE-SCHOOL.NET
Remember:

y-intercept ⇒ x = 0
cut y-axis ⇒ x = 0
x-intercept ⇒ y = 0
cut x-axis ⇒ y = 0
**point lies on the line ⇒ satisfy the equation ⇒ substitute the value of x and of y of the point into the
equation.

Equation of Locus
( use the formula of                The equation of the locus of a           The equation of the locus of a moving
distance)                           moving point P ( x, y ) which is         point P ( x, y ) which is always
The equation of the locus of a      always at a constant distance            equidistant from two fixed points A and B
moving point P ( x, y ) which       from        two    fixed        points   is the perpendicular bisector of the
is always at a constant             A ( x1 , y1 ) and B ( x2 , y 2 ) with    straight line AB.
distance (r) from a fixed point     a ratio m : n is
A ( x1 , y1 ) is                                                                                 PA = PB
PA m
2
( x − x1 ) + ( y − y1 ) 2 = ( x − x2 ) 2 + ( y − y2 ) 2
=
PA = r                                PB n
( x − x1 ) 2 + ( y − y1 ) 2 = r 2   ( x − x1 ) 2 + ( y − y1 ) 2 m 2
=
( x − x2 ) + ( y − y 2 ) 2 n 2

More Formulae and Equation List:

SPM Form 4 Physics - Formulae List
SPM Form 5 Physics - Formulae List

SPM Form 4 Chemistry - List of Chemical Reactions
SPM Form 5 Chemistry - List of Chemical Reactions

All at

http://www.one-school.net/notes.html                         6
ONE-SCHOOL.NET
07 Statistics
Measure of Central Tendency

Grouped Data
Ungrouped Data
Without Class Interval                             With Class Interval
Mean
Σx                                        Σ fx                                               Σ fx
x=                                         x=                                                 x=
N                                         Σf                                                 Σf

x = mean                                   x = mean                                     x = mean
Σx = sum of x                              Σx = sum of x                                f = frequency
x = value of the data                      f = frequency                                x = class mark
N = total number of the                    x = value of the data
data                                                                                         (lower limit+upper limit)
=
2
Median
m = TN +1                                  m = TN +1                                          ⎛ 1N −F⎞
2                                          2                                m = L+ ⎜ 2
⎜ f    ⎟C
⎟
When N is an odd number.                    When N is an odd number.                                     ⎝    m ⎠

m = median
TN + TN                                    TN + T N                        L = Lower boundary of median class
+1                                         +1
m=      2            2
m=        2         2                 N = Number of data
2                                              2                      F = Total frequency before median class
When N is an even                       When N is an even number.                   fm = Total frequency in median class
number.                                                                          c = Size class
= (Upper boundary – lower boundary)

Measure of Dispersion

Grouped Data
Ungrouped Data
Without Class Interval          With Class Interval

variance
σ =2∑ x2                   −x
2
σ =
2 ∑ fx 2                −x
2
σ =
2 ∑ fx 2        −x
2

N                                  ∑f                                                 ∑f
σ = variance                                σ = variance                                       σ = variance

Σ(x − x )
2
Σ(x − x )
2
Standard                                                                                                           Σ f (x − x)
2
σ=                                          σ=
Deviation              N                                                        N                               σ=
Σf
Σx 2                                          Σx 2
σ=              − x2                        σ=                − x2                                   Σ fx 2
N                                             N                                    σ=           − x2
Σf

http://www.one-school.net/notes.html                                         7
ONE-SCHOOL.NET

The variance is a measure of the mean for the square of the deviations from the mean.

The standard deviation refers to the square root for the variance.

Effects of data changes on Measures of Central Tendency and Measures of dispersion

Data are changed uniformly with
+k        −k         ×k        ÷k
Measures of    Mean, median, mode                             +k        −k         ×k        ÷k
Central Tendency
Range , Interquartile Range                          No changes                ×k      ÷k
Measures of
Standard Deviation                                   No changes                ×k      ÷k
dispersion
Variance                                             No changes                × k2    ÷ k2

08 Circular Measures
Terminology

Convert degree to radian:
Convert radian to degree:
π
xo = ( x ×      )radians
180                                                        180
×
π                                                             180
x radians = ( x ×     ) degrees
π

π
×
180

Remember:

O
???    0.7 rad                           ???
360 = 2π rad

http://www.one-school.net/notes.html                 8
ONE-SCHOOL.NET
Length and Area

A = area
s = arc length
θ = angle
l = length of chord

Arc Length:          Length of chord:     Area of Sector:       Area of Triangle:         Area of Segment:

s = rθ                          θ             1 2                     1 2                 1 2
l = 2r sin            A=     rθ           A=         r sin θ      A=     r (θ − sin θ )
2             2                       2                   2

09 Differentiation

Differentiation of a Function I
Gradient of a tangent of a line (curve or
straight)                                                    y = xn
dy        δy                                dy
= lim ( )                                   = nx n−1
dx δ x →0 δ x                               dx

Example
y = x3
Differentiation of Algebraic Function
dy
Differentiation of a Constant                                    = 3x 2
dx
y=a          a is a constant
dy
=0                                             Differentiation of a Function II
dx
y = ax
Example                                                  dy
y=2                                                         = ax1−1 = ax 0 = a
dx
dy
=0
dx                                                      Example
y = 3x
dy
=3
dx

http://www.one-school.net/notes.html                9
ONE-SCHOOL.NET
Differentiation of a Function III                Chain Rule

y = ax n                                      y = un       u and v are functions in x
dy                                            dy dy du
= anx n−1                                    =  ×
dx                                            dx du dx

Example                                        Example
y = 2 x3                                       y = (2 x 2 + 3)5
dy                                                                           du
= 2(3) x 2 = 6 x 2                         u = 2 x 2 + 3,     therefore      = 4x
dx                                                                           dx
dy
y = u5 ,    therefore       = 5u 4
du
Differentiation of a Fractional Function
dy dy du
=     ×
1                                          dx du dx
y=
xn                                           = 5u 4 × 4 x
Rewrite                                           = 5(2 x 2 + 3) 4 × 4 x = 20 x(2 x 2 + 3) 4
y = x−n
dy                −n                          Or differentiate directly
= − nx − n−1 = n+1                         y = (ax + b) n
dx               x
dy
= n.a.(ax + b) n −1
Example                                        dx
1
y=
x                                          y = (2 x 2 + 3)5
y = x −1                                       dy
= 5(2 x 2 + 3) 4 × 4 x = 20 x(2 x 2 + 3) 4
dy           −1                                dx
= −1x −2 = 2
dx           x

Law of Differentiation

Sum and Difference Rule

y =u±v   u and v are functions in x
dy du dv
=   ±
dx dx dx

Example
y = 2 x3 + 5 x 2
dy
= 2(3) x 2 + 5(2) x = 6 x 2 + 10 x
dx

http://www.one-school.net/notes.html        10
ONE-SCHOOL.NET
Product Rule                                                      Quotient Rule

y = uv    u and v are functions in x                                   u
y=             u and v are functions in x
dy     du    dv                                                        v
= v +u
dx     dx    dx                                                                du    dv
v      −u
dy           dx    dx
=
Example                                                            dx              v2
y = (2 x + 3)(3 x 3 − 2 x 2 − x)
Example
u = 2x + 3           v = 3x3 − 2 x 2 − x
x2
du                 dv                                            y=
=2                = 9 x2 − 4 x − 1                               2x +1
dx                 dx
u = x2           v = 2x +1
dy     du     dv
=v      +u                                                    du                  dv
dx     dx     dx                                                     = 2x                =2
dx                  dx
=(3 x − 2 x − x)(2) + (2 x + 3)(9 x 2 − 4 x − 1)
3     2
du      dv
v    −u
dy
= dx 2 dx
Or differentiate directly                                         dx         v
y = (2 x + 3)(3x3 − 2 x 2 − x)                                    dy (2 x + 1)(2 x) − x 2 (2)
=
dy                                                               dx          (2 x + 1) 2
= (3x3 − 2 x 2 − x)(2) + (2 x + 3)(9 x 2 − 4 x − 1)
dx                                                                    4 x2 + 2 x − 2 x2 2 x2 + 2 x
=                  =
(2 x + 1) 2     (2 x + 1) 2

Or differentiate directly
x2
y=
2x +1
dy (2 x + 1)(2 x) − x 2 (2)
=
dx         (2 x + 1) 2
4 x2 + 2 x − 2 x2 2 x2 + 2 x
=                  =
(2 x + 1) 2     (2 x + 1) 2

http://www.one-school.net/notes.html                         11
ONE-SCHOOL.NET
Gradients of tangents, Equation of tangent and Normal

Gradient of tangent at A(x1, y1):

dy
= gradient of tangent
dx

Equation of tangent: y − y1 = m( x − x1 )

Gradient of normal at A(x1, y1):

1
mnormal = −
mtangent
If A(x1, y1) is a point on a line y = f(x), the gradient                  1
of the line (for a straight line) or the gradient of the                        = gradient of normal
− dy
dy                    dx
tangent of the line (for a curve) is the value of
dx          Equation of normal : y − y1 = m( x − x1 )
when x = x1.

Maximum and Minimum Point

dy
Turning point ⇒        =0
dx

At maximum point,                                          At minimum point ,
2
dy                 d y                                       dy                d2y
=0                   <0                                      =0                  >0
dx                 dx 2                                      dx                dx 2

http://www.one-school.net/notes.html                   12
ONE-SCHOOL.NET
Rates of Change                                  Small Changes and Approximation
Small Change:
dA dA dr
Chain rule      =  ×
dt dr dt                            δ y dy        dy
≈   ⇒ δ y ≈ ×δ x
δ x dx        dx
dx
If x changes at the rate of 5 cms -1 ⇒
=5            Approximation:
dt
Decreases/leaks/reduces ⇒ NEGATIVES values!!!                 ynew = yoriginal + δ y
dy
= yoriginal +      ×δ x
dx

δ x = small changes in x
δ y = small changes in y
If x becomes smaller ⇒ δ x = NEGATIVE

http://www.one-school.net/notes.html            13
ONE-SCHOOL.NET
10 Solution of Triangle

Sine Rule:                         Cosine Rule:                            Area of triangle:
a
a     b     c                    a2 = b2 + c2 – 2bc cosA
=     =                       b2 = a2 + c2 – 2ac cosB
sin A sin B sin C                                                        C
c2 = a2 + b2 – 2ab cosC
b
Use, when given
2 sides and 1 non included                          b2 + c2 − a 2
cos A =
angle                                                   2bc                             1
2 angles and 1 side                                                                A=     a b sin C
2
Use, when given
2 sides and 1 included angle           C is the included angle of sides a
a               a    B         3 sides                                and b.
A
A                          a                     a        c
b         180 – (A+B)
A
b                     b

http://www.one-school.net/notes.html                   14
ONE-SCHOOL.NET

Case of AMBIGUITY                           If ∠C, the length AC and length AB remain unchanged,
the point B can also be at point B′ where ∠ABC = acute
A
and ∠A B′ C = obtuse.
If ∠ABC = θ, thus ∠AB′C = 180 – θ .
180 - θ
θ                                Remember : sinθ = sin (180° – θ)
C                B′             B
Case 1: When a < b sin A                                   Case 2: When a = b sin A
CB is too short to reach the side opposite to C.           CB just touch the side opposite to C

Outcome:                                                   Outcome:
No solution                                                1 solution
Case 3: When a > b sin A but a < b.                        Case 4: When a > b sin A and a > b.
CB cuts the side opposite to C at 2 points                 CB cuts the side opposite to C at 1 points

Outcome:                                                   Outcome:
2 solution                                                 1 solution

Useful information:
In a right angled triangle, you may use the following to solve the
c                     problems.
b                                               (i) Phythagoras Theorem: c = a 2 + b2
θ
a                                           Trigonometry ratio:
(ii)
sin θ = b , cos θ = a , tan θ =
c           c
b
a

(iii) Area = ½ (base)(height)

http://www.one-school.net/notes.html                   15
ONE-SCHOOL.NET
11 Index Number
Price Index                                                   Composite index

P                                                          Σ Wi I i
I =    1
× 100                                              I=
P0                                                          Σ Wi

I = Price index / Index number                                  I = Composite Index
P0 = Price at the base time                                      W = Weightage
P1 = Price at a specific time
I = Price index

I A, B × I B ,C = I A,C ×100

http://www.one-school.net/notes.html                       16

```
To top